Pengaruh Kompetensi, Fee, Audit Tenure, Audit Firm Size dan Skala Entitas Klien Terhadap Kualitas Audit - Ninik Zawafa Ulfa Richah; Ni Nyoman Alit Triani (Universitas Muhammadiyah Enrekang, 2021)
The purpose of this study is to analyze the effect of competence, audit fees, audit engagement period, size of public accounting firm and client entity scale on audit quality. The existence of this research is expected to improve the quality of audit services provided to clients in the future. The population of this study is publicly traded companies in the trade, service and investment industry listed on the IDX from 2014 to 2018. The sampling technique for this study was purposive sampling technique with a total sample size of 485 data. This study uses a logistic regression model analysis technique. This study found that the audit fee variable and audit firm size have a positive effect on audit quality. The client entity scale variable shows a negative influence on the level of audit quality. Meanwhile, the auditor competence variable and the audit engagement period variable showed no significant effect on audit quality.